“Surviving Discrimination by Pulling Together”: LGBTQI Cancer Patient and Carer Experiences of Minority Stress and Social Support - Power, Rosalie; Ussher, Jane M.; Perz, Janette; Allison, Kimberley; Hawkey, Alexandra J. (Frontiers in Oncology, 2022)
Background: Lesbian, gay, bisexual, transgender, queer and/or intersex (LGBTQI) people with cancer and their carers report poorer psychological outcomes than the general non-LGBTQI cancer population. There is growing acknowledgement that these health inequities can be explained by minority stress, which can be buffered by social support. Study Aim: To examine subjective experiences of minority stress and social support for LGBTQI people with cancer and their carers, drawing on qualitative findings from the Out with Cancer study. Method: An online survey including open ended items was completed by 430 LGBTQI cancer patients and 132 partners and other carers, representing a range of tumor types, sexual and gender identities, age and intersex status. A sub-sample of 104 patients and 31 carers completed an interview, with a follow-up photovoice activity and second interview completed by 45 patients and 10 carers. Data was thematically analysed using an intersectional theoretical framework. Results: Historical and present-day experiences of discrimination, violence, family rejection and exclusion created a legacy of distress and fear. This impacted on trust of healthcare professionals and contributed to distress and unmet needs in cancer survivorship and care. Social support, often provided by partners and other chosen family, including intimate partners and other LGBTQI people, buffered the negative impacts of minority stress, helping LGBTQI patients deal with cancer. However, some participants lacked support due to not having a partner, rejection from family of origin and lack of support within LGBTQI communities, increasing vulnerability to poor psychological wellbeing. Despite the chronic, cumulative impacts of minority stress, LGBTQI patients and carers were not passive recipients of discriminatory and exclusion in cancer care, demonstrating agency and resistance through collective action and advocacy. Conclusion: LGBTQI people have unique socio-political histories and present-day psycho-social experiences that contribute to distress during cancer. Social support serves to buffer and ameliorate this distress. Cancer healthcare professionals and support services need to be aware of and responsive to these potential vulnerabilities, including the intersectional differences in experiences of minority stress and social support. There is also a need for recognition and facilitation of social support among LGBTQI people with cancer and their carers.